On the Assumptions and Postulates of Cultural Linguistics (On the Example of the Definition of Polish PRACA (‘WORK’)) - Bartmiński, Jerzy (Vilnius University Open Series, 2020)
The study consists of four parts. The first part is devoted to the beginnings of cultural linguistics in Poland, connected with the Wrocław-based programme for research on Polish national culture, the emergence of the “Language and Culture” research network (and a publication series with the same title), and the launch of the Lublin-based journal Etnolingwistyka in 1988. The second part contains examples of linguistic facts being viewed in cultural perspective, with a special role of the lexicon as the “mirror of culture”. Part three presents a repertoire of seven conceptual constructs proposed in Lublin cognitive ethnolinguistics (linguistic worldview, stereotypes as cultural concepts, cognitive definition, viewpoint and interpretive perspective, profiling of base images, values, and the experiencing, conceptualizing, and speaking subject). Finally, the fourth part illustrates the application of this theoretical framework in an analysis of the Polish cultural concept of PRACA ‘WORK’.
Keywords: cultural linguistics; Język a Kultura (‘Language and Culture’) series; Etnolingwistyka yearly journal; Lublin cognitive ethnolinguistics; linguistic worldview; cultural concept; PRACA / WORK